Novel solar sail mission concepts for high-latitude earth and lunar observation - Heiligers, Jeannette; Parker, Jeffrey S.; Macdonald, Malcolm (Journal of Guidance, Control, and Dynamics, 2017)
This paper proposes the use of solar sail periodic orbits in the Earth-Moon system for observation of the high-latitudes of the Earth and Moon. At the Earth, the high-latitudes will be crucial in answering questions concerning global climate change, monitoring space weather events and ensuring sustainable development of these fragile regions. The polar regions of the Moon, especially the South Pole, are of great scientific interest as well as a potential destination for a future permanent lunar base. The existence of families of solar sail periodic orbits in the Earth-Moon system has previously been demonstrated by the authors and is expanded in this paper by introducing additional orbit families. The paper focuses in particular on orbits that are achievable with near-term solar sail technology and that originate by maintaining the solar sail at a constant attitude with respect to the Sun such that mission operations are greatly simplified. The results provide a set of constellations for continuous observation of the high-latitudes. For example, a constellation of two solar sail L2-displaced vertical Lyapunov orbits can achieve continuous observation of both the lunar South Pole and the centre of the Aitken Basin at a minimum elevation of 15 deg, while at the Earth, a set of two, so-called 'clover-shaped' orbits can provide continuous coverage of one of the Earth's Poles at 20 deg minimum elevation. Transferring these orbits to a higher-fidelity model, taking among others the eccentricity of the Moon into account, shows that these orbits still exist without any significant impact on their performance for high-latitude observation of the Earth and Moon.